Verbzweitsätze aus kontrastiver Sicht (Deutsch-Italienisch): Das topologische Modell zur Verbstellung - MALLOGGI, PATRIZIO (Glottodidactica, 2019)
The present paper focuses on the syntactic description of verb-second-sentences from a contrastive view (German-Italian). The study is based upon a corpus of texts written by Italian native speakers of the course German Language for Tourism at the University of Pisa. This paper is composed of two parts: the first one aims at pointing out the main grammatical structural differences between Italian and German declarative sentences as far as the position of the verb is concerned; the second one shows the results gained by analysing the corpus of written texts referring to the position of the verb in declarative sentences in order to provide a successful methodological approach to verb-second-sentences in the didactics of German as foreign language.